Penerapan Teknologi Augmented Reality dalam Sistem Katalog Interaktif Menggunakan Metode Marker Based Berbasis Android (Studi Kasus : Toko Tas Bogor) - Dwi Noor Saputra; Sri Rama Putri (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
The purpose of the research on the bogor bag store using Aungmented Reality(AR) based on Android is to combine the real world with the virtual one through direct media, allowing 3D objects created by a computer to be viewed in their entirety using the developed application. Augmented Reality can provide information about the product sold by the Bogor bag store, such as viewing bags from all angles and displaying information about the bags available for sale. The goal is to create an Augmented Reality application that can be used as a promotional medium for an interactuve catalog and an egaging experience for consumers, helping them in selecting products from the Bogor bag store. The methods used are data collection, interviews, literatur study, and observation. Marker based is a term used to combine the real world and the virtual world, where objects in the real world are recognized through their position, orientation, and location. The process is conducted on an Android basis, allowing users to view bags in 3D, and store owners do not need to carry the actual bags. This Botor bag store application is designed using Augmented Reality (AR), Android, and Unity. The proposed design system consists og three stages : use case fiagram, activity diagram, and class diagram. The tools used Unity, Cuforia, JDK, SDK, and Blender. Conclusion un this study, an application was created that provides product information fot Bogor bag store and makes it easier for shop owners not tp carry original bags in marketing.